Antioxidant activities (DPPH and ABTS method) from extract of Bangle rhizome (Zingiber cassumunar) using different method of extraction - Kartika Sari; Anton Rahmadi; Miftakhur Rohmah; Bernatal Saragih; Iddris Salam (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Antioxidants are important for the prevention of oxidative stress, which can cause various degenerative diseases. Bangles contain bioactive components with antioxidant potential. Processing affects the active compounds in food, including angle. This study aimed to determine the effects of the blanching and extraction methods on the antioxidant activity of Bangle. This study focused on three factors: blanching treatment extraction technique, time, and type of extraction solvent. Analyses of antioxidants using the DPPH and ABTS methods were conducted in triplicate for each sample. Data were analyzed using ANOVA. The results of this study show that the method, time, and type of solvent significantly affect the antioxidant activity of bangle rhizome extracts. The best treatment for antioxidant activity of Bangle rhizome was blanching treatment by adding 0,05% citric acid solution in the sonication extraction method for 30 min with ethanol as the solvent. The IC50 value on the DPPH method was 20,61±0,76 mg/g, and the percent free radical scavenging value was 87,11±3,04%. The IC50 value on the ABTS method is 20,79±0,29 mg/g and a percent free radical scavenging activity value of 92,75±0,13%. This study provides key insights for choosing effective extraction methods to increase antioxidant activity in natural materials, such as Bangle rhizomes.